The Administrative System of the European Union - From Concept to Reality - Lucica MATEI; Ani MATEI (Transylvanian Review of Administrative Sciences, 2011)
At the beginning of the 21st century, the European Union (EU) governance and administration are undergoing some significant transformations, not without obstacles, from concept to reality, revealing characteristics that aim both the European and national elements in a permanent interpenetration, whose complexity is superior to other processes and phenomena specific for the construction of a United Europe. The major objective of the current paper is to substantiate and describe systemically the process of affirmation and transformation of the EU administration as a core pillar of European governance. A doctrinal overview on the debated topic reveals an atypical concept in terms of the traditional approach in administrative sciences, thus leading in the specialized studies to controversies going to the conceptual negation of the EU administration. This time, the reality of EU construction anticipates traditional theories and doctrines, imposing even a change of vision, getting closer to the modern theories of public management and administration. The EU administration has developed simultaneously with the construction of the United Europe on a distinct area that overlaps with the EU area in its various enlargement stages. In a regulatory perspective, the EU administration has benefited due to the constitutive treaties, from a contextual ground containing relatively few direct and explicit assertions, but which valorize the European traditions and culture, mainly in the Member States, integrating creatively the international developments of public management. In a developing relation, we witness a permanent adaptation of the EU administration to the needs arising from the achievement of the EU objectives. The attempt to institute an ‘EU Constitution’ got the doctrinal approach of the EU administration closer to the traditional approach specific for the European legal systems. The failure of that activity has created a new impetus to a different approach encompassing even features of a significant reform expressed in the Lisbon Treaty that entered into force on December 1st 2009. Taking into consideration the background of the European integration, the studies and researches highlight that the main processes of the EU administration construction consist of Europeanization, administrative convergence and dynamics. In a systemic approach they become mechanisms of adjustment and self-adjustment in a social dynamic system, with multi poles and mixed architecture, such as that of the EU administration